Design and Synthesis of a Biochar-Supported Nano Manganese Dioxide Composite for Antibiotics Removal From Aqueous Solution - Li, Jiang; Cai, Xiaoxi; Liu, Yunguo; Gu, Yanling; Wang, Hui; Liu, Shaobo; Liu, Simian; Yin, Yicheng; Liu, Sijia (Frontiers in Environmental Science, 2020)
Manganese dioxide nanoparticles were loaded onto biochar prepared from rice husk to obtain a biochar-supported manganese dioxide composite (BC/MnO2). The properties of this composite were studied through various advanced characterization techniques, combined with experiments on treating aqueous solutions of tetracycline hydrochloride (TC) and doxycycline (DC). The results showed that compared with the original biochar, MnO2 nanoparticles appeared on the surface of BC/MnO2, the carbon content decreased, and the oxygen content increased. Moreover, BC/MnO2 exhibited significantly larger total pore volume and specific surface area, and the pore structure of the biochar was improved. The effect of pH on the adsorption of TC and DC by BC/MnO2 was insignificant. With an increase in the adsorbent dose, the removal rates of TC and DC increased, and the removal ability of BC/MnO2 for TC was slightly higher than that for DC. The adsorption of TC and DC on the BC/MnO2 surface conformed to the Freundlich model. Compared with the pseudo-first-order kinetic model, the pseudo-second-order kinetic model (R2 = 0.999) better fitted the adsorption data, indicating that the adsorption process is controlled by chemical adsorption. In addition, the results of adsorption-desorption experiments indicated that BC/MnO2 have excellent regeneration ability. The experimental results of this study are significant for expanding the application of biochar composites in the treatment of aqueous solution containing antibiotics.